The Impact of Corporate Social Responsibility and Internal Marketing on Employee Turnover Intentions with the Mediating Role of Organizational Commitment - Boudlaie, Hasan; Keshavarz Nik, Behrouz; Kenarroodi, Mohammadhosein (Technium Social Sciences Journal, 2021)
Abstract. Employee turnover is one of the most important phenomena in the study of individuals' organizational behavior. For this reason, organizations able to identify effective factors in employee turnover are more likely to employ more effective policies and methods to maintain their human resources before they leave the organization. This study aims to investigate the impact of corporate social responsibility and internal marketing on employee turnover intentions, considering the mediating role of organizational commitment. The present research is practical in purpose, descriptive in data collection methodology and a survey research in type. The research population consisted of all employees in all Tehran branches of the Melli Bank of Iran, amounting to 9405 people. The Cochran formula was used to determine the sample size, which yielded a sample size of 369 people. This research employs the clustering method for sampling and a standard survey for data collection. The statistical method utilized in this study is the structural equation method and all statistical analysis was performed using SPSS19 and AMOS23 softwares. Testing the research hypotheses revealed that social responsibility and internal marketing have a positive and significant effect on organizational commitment and organizational commitment has a significant negative impact on employee turnover intentions. Also, organizational commitment completely mediates the negative impact of social responsibility and internal marketing on the employee turnover intentions.